2016
DOI: 10.1111/jam.13260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus formosensis S215T and Lactobacillus buchneri on quality and in vitro ruminal biological activity of condensed tannins in sweet potato vines silage

Abstract: Lactobacillus formosensis has the potential to be used as a silage inoculant because of its ability to improve fermentability and aerobic stability in sweet potato vines silage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…In the present study, the fermentation quality of the SPV and CF silages showed lower lactic acid concentration but higher pH value and acetic acid concentration than those reported in previous studies using silages ensiled with more short‐length materials (Van Man & Wiktorsson ; Mangwe et al . ). Although chopping length might affect such high pH values for both the experimental silages, especially for the CF silage, more short‐cutting (approximately 3 cm length by a cutting machine) CF silages prepared in another experiment showed similar higher pH values after 3 months ensiling (H.L.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, the fermentation quality of the SPV and CF silages showed lower lactic acid concentration but higher pH value and acetic acid concentration than those reported in previous studies using silages ensiled with more short‐length materials (Van Man & Wiktorsson ; Mangwe et al . ). Although chopping length might affect such high pH values for both the experimental silages, especially for the CF silage, more short‐cutting (approximately 3 cm length by a cutting machine) CF silages prepared in another experiment showed similar higher pH values after 3 months ensiling (H.L.…”
Section: Discussionmentioning
confidence: 97%
“…The previous study reported that applied Lactobacillus formosensis in SPV silage reduced DM loss and increased in vitro rumen N digestibility [ 23 ]. Also, application of LAB as silage inoculants potentially increased the digestibility in rumen [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic stability is an important parameter in determining SPV silage quality considering its high WSC content. After ensiled, original SPV silage still contains a lot of WSC, approximately 13.9% of DM [ 23 ]. Silage treated with LB resulted in the highest aerobic stability, particularly LB silage was 4 times greater (149.2 vs 36.4 h) than LP silage in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the use of sweet potato by-product in livestock diet is a promising reality, with great potential for application and positive effects as to weight gain, and organic matter consumption and digestibility (Megersa, Urge, & Nurfeta, 2013;Phesatcha & Wanapat, 2013;Beckford & Bartlett, 2015;Mangwe, Rangubhet, Mlambo, Yu, & Chiang, 2016;Dang et al, 2017;Li, Ji, Wang, Qin, Hou, & Shen, 2017;Kamiya et al, 2017), but few studies have assessed the effect of using sweet potato on ruminal pH; what has been proposed is the transformation of a residue, which is not commercialized, into flour or bran, in order to compose a balanced diet. Therefore, the objective of this study is to assess the ruminal pH of sheep supplemented with different levels of sweet potato byproduct.…”
Section: Introductionmentioning
confidence: 99%